Pengaruh Project Based Learning Terintegrasi Entrepreneurship pada Materi Pencemaran Lingkungan Terhadap Motivasi dan Kemampuan Berpikir Kreatif - Kamisah Kamisah; Wilda Syahri; Syamsurizal (BIOEDUSAINS:Jurnal Pendidikan Biologi dan Sains, 2025)
This study aimed to examine the effect of a Project Based Learning (PjBL) model integrated with entrepreneurship on students’ motivation and creative thinking skills in the topic of environmental pollution. The method used was a quasi-experiment with a NonEquivalent Control Group Design. The research design employed a Pretest-Posttest Control Group Design, with a total sampling technique, involving class X Nursing A as the experimental group and class X Nursing B as the control group, each consisting of 20 students. The results showed that the average motivation score in the experimental class was 98.70, while in the control class it was 95.45. The Independent Sample t-test revealed a significance value of 0.037 < 0.05, indicating a significant difference in learning motivation between the two classes. The analysis of creative thinking skills showed an average score of 79.75 in the experimental class and 75.25 in the control class, with a significance value of 0.029 < 0.05, indicating a significant difference in creative thinking skills between the groups. In conclusion, the implementation of the PjBL model integrated with entrepreneurship effectively enhances students’ motivation and creative thinking skills in the topic of environmental pollution.   Keywords: Creative Thinking, Entrepreneurship, Motivation, PJBL, Environmental Pollution